Ghana : Staff Report for the 2001 Article IV Consultation and the Third Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2001)
The Ghanaian economy suffered a fallout from the large terms-of-trade shock that began in 1999. The fiscal program adopted is prudent and faces up to the country's difficult economic circumstances. Effective control of public expenditure commitments will be essential to the success of the program. Monetary policy will have to remain reasonably tight in the very near term. The IMF staff welcomes the new government's emphasis on mobilizing the private sector, its anticorruption campaign, and transparency in its dealings.